Employing the CORT program to develop innovative thinking and address learning difficulties in handicrafts (Journal of the College of Basic Education, 2023)
Education is the means of education in achieving its objectives and an important source in building the human personality. It works to strike a balance between the needs of the individual learner and the requirements of the comprehensive development of his society. This poses great challenges for curriculum planners, education designers and implementers, represented in setting general and specific educational goals, identifying students’ characteristics, needs and abilities, analyzing educational content, building spoken tests, developing educational strategies, and investing in modern technology developments to meet the needs of the individual and society in a manner that is consistent with the spirit of the times and the studies. Educational and psychological (Al-Hilah, 1998, p. 13), as well as facing educational and technical problems and other complexities of the age, and the aim of education - in this regard - is not merely to teach ready-made information, but rather to work to provide the learner with methods of thinking and problem-solving, to be able to produce knowledge It is not just memorizing and consuming it, and this is the path of creativity and innovators (Hanoura, 1999, p. 42).